THE EFFECTIVENESS OF TEAM BASED PROJECT LEARNING MODEL IN ENGLISH DRAMA COURSE - Ayu Melati Ningsih; Risnawaty Risnawaty; Zulfitri Zulfitri (PROJECT (Professional Journal of English Education), 2023)
Team based project short film-based is the implementation of the course english drama which is one of the courses in the English literature study program that studies English literary works. The aims of this study were; (1) to increase student creativity through learning models team based project based on short films, (2) knowing the effectiveness of learning models team based project on courses english drama. The method used in this research is descriptive-qualitative. Methods of data collection using observation, interviews and documents. The results of the research show the learning model team based project  effectively used in courses english drama and making short films that are uploaded on YouTube in accordance with the creativity of students who have been guided in the theoretical material sessions that have been given by the course lecturer. The stages of the project using team based project short film based is; (1) students discuss related to the theme of the short film according to the course, (2) write scripts, (3) students carry out project activities according to the timeline that has been prepared, (4) students edit films and upload them to social media youtube. The outputs targeted in this study are international journals, sinta 3 accredited journals and monograph books. Keywords:  Team Based Project; Short Film;  English Drama